Health Equity Assessment Toolkit (HEAT and HEAT Plus): exploring inequalities in the COVID-19 pandemic era. - Kirkby, Katherine; Schlotheuber, Anne; Vidal Fuertes, Cecilia; Ross, Zev; Hosseinpoor, Ahmad Reza (International Journal for Equity in Health, 2022)
Background: The Sustainable Development Goals have helped to focus attention on the importance of reducing inequality and 'leaving no one behind'. Monitoring health inequalities is essential for providing evidence to inform policies, programmes and practices that can close existing gaps and achieve health equity. The Health Equity Assessment Toolkit (HEAT and HEAT Plus) software was developed by the World Health Organization to facilitate the assessment of within-country health inequalities. Results: HEAT contains a built-in database of disaggregated health data, while HEAT Plus allows users to upload and analyze inequalities using their own datasets. Version 4.0 of the software incorporated enhancements to the toolkit's capacity for equity assessments. This includes a multilingual interface, interactive and downloadable visualizations, flexibility to analyze inequalities using any dataset of disaggregated data, and the built-in calculation of 19 summary measures of inequality. This paper outlines the improved features and functionalities of the HEAT and HEAT Plus software since their original release, highlighted through an example of how the toolkit can be used to assess inequalities in the COVID-19 pandemic era. Conclusions: The features of the HEAT and HEAT Plus software make it a valuable tool for analyzing and reporting inequalities related to the COVID-19 pandemic, as well as its indirect impacts on inequalities in other health and non-health areas, providing evidence to inform equity-oriented interventions and strategies.